Network Management for Preventing and Resolving Human Trafficking Issues in Chonburi Province, Thailand - Santad, Patchara; Ratchadapunnathikul, Chet (Asian Crime and Society Review, 2019)
The objective of this research is to study, analyze, and synthesize network management for preventing and resolving human trafficking issues in human trafficking. A qualitative approach, including in-depth interview, group discussion, and network forum among 33 main informants, were used for data collection. Content analysis was bringing to apply afterwards. From the study, it has been found that network management for preventing and resolving human trafficking in Chonburi province are applied at both provincial and district levels. At the provincial level, the Provincial Office of Social Development and Human Security is the operational center that helps the affected persons, in collaboration with the police, the Provincial Office of Labor Protection and Welfare, the Provincial Office of Employment, and the Provincial Office of Public Health. In addition, training sessions are organized to educate workers and business owners. At the district level, the Provincial Office of Social Development and Human Security, the local police, and sub-district health promoting hospitals, with the chief district officer as the head of the working team. The suggestions include involving all agencies in the network in resolving human trafficking problems in order to unify the team and maximize the efficiency, improving human trafficking-related data organization system to make it more up-to-date and accessible to all relevant parties, expanding the collaboration to the public and other networks in the community to monitor and resolve human trafficking issues.